Miniaturization of terahertz time domain spectroscopy (THz) - Thean, Lester Zhi Hui (Nanyang Technological University, 2024)
Terahertz waves has been proven to be useful in a variety of applications across diverse studies, ranging from condensed matter physics and gas-phase spectroscopy to biomedical imaging, with even suggestions for usage in outer space. However, as of April 2024, terahertz is still restricted to research purposes instead of the domestic market due to the logistical and practical challenges for the usage of Terahertz. The terahertz (THz) spectral region, spanning from 300 GHz (λ= 1 mm) to 10 THz (λ = 30 μm), is still relatively underdeveloped compared to optical or microwave frequencies. In general, THz spectroscopy can be broadly separated into measurements of gases and that of liquids and solids. At the low number density characteristic of gases, frequency of collisions between molecules determines dephasing times that occur on time scales generally much longer than 1 ps. It is worth noting that considerable research on the development of photoconductive THz emitters for specific applications have been done, where the detection and generation of THz pulses, the usage of photo conductively gated antennas shares the same physical principles. Properties such as antenna design and semiconductor properties can critically affect THz detection.